HASIL PETSAY AKIBAT PEMBERIAN PUPUK ORGANIK CAIR BERBAHAN UTAMA LIMBAH TAHU - Dolfiana Boek; Nova D. Lussy; Lena Walunguru (Politeknik Pertanian Negeri Kupang, 2023)
The purpose of this study was to examine the effect and obtain the best concentration of tofu waste liquid organic fertilizer (LOF) on the yield of petsay plants. This research was conducted from April to June 2020 in Noelbaki Village. The design used was a randomized group design (RGD) with eight treatments namely without application of tofu waste LOF; concentration of tofu waste LOF: 10, 15, 20 25, 30, 35, and 40 ml/l. The parameters observed are crop length, crop diameter, crop fresh weight, and crop dry weight. The results of the study are the provision of tofu waste LOF has a significant effect on the crop length, crop diameter, crop fresh weight, and crop dry weight. Tofu waste LOF at a concentration of 35 ml/l has best concentration on crop length (26.50 cm), crop diameter (8.60 cm), crop fresh weight (572.60 g), and crop dry weight (52.60 g). Keywords: LOF, tofu waste, concentration, petsay, crop